Keeping the promise: a critique of the current state of microdosing research - Petranker, Rotem; Anderson, Thomas; Fewster, Emily C.; Aberman, Youval; Hazan, Marik; Gaffrey, Michael; Seli, Paul (Frontiers in Psychiatry, 2024)
Introduction The practice of taking small, sub-hallucinogenic doses of psychedelics, known as microdosing, has exploded in popularity over the last decade. Users claim benefits ranging from improved mood and enhanced creativity to an increased sense of meaning and connectedness in life. While research on microdosing is still lagging behind the shift in public opinion, several papers have been published in the last five years which attempted to assess the effects of microdosing. Methods This review paper aimed to critically analyze the research practices used in the recent wave of microdosing research: We reviewed 15 papers published before the closing date of this review in March 2022. Results Our review concludes that it is premature to draw any conclusions about the efficacy or safety of microdosing since the research quality cannot be considered confirmatory. Discussion We propose some potential causes for the current state of the literature and some suggestions for how these causes may be ameliorated.